SiRNA Therapeutics against Respiratory Viral Infections—What Have We Learned for Potential COVID‐19 Therapies?. Issue 7 (27th January 2021) - Mehta, Aditi; Michler, Thomas; Merkel, Olivia M.
Abstract: Acute viral respiratory tract infections (AVRIs) are a major burden on human health and global economy and amongst the top five causes of death worldwide resulting in an estimated 3.9 million lives lost every year. In addition, new emerging respiratory viruses regularly cause outbreaks such as SARS‐CoV‐1 in 2003, the "Swine flu" in 2009, or most importantly the ongoing SARS‐CoV‐2 pandemic, which intensely impact global health, social life, and economy. Despite the prevalence of AVRIs and an urgent need, no vaccines—except for influenza—or effective treatments were available at the beginning of the COVID‐19 pandemic. However, the innate RNAi pathway offers the ability to develop nucleic acid‐based antiviral drugs. siRNA sequences against conserved, essential regions of the viral genome can prevent viral replication. In addition, viral infection can be averted prophylactically by silencing host genes essential for host–viral interactions. Unfortunately, delivering siRNAs to their target cells and intracellular site of action remains the principle hurdle toward their therapeutic use. Currently, siRNA formulations and chemical modifications are evaluated for their delivery. This progress report discusses the selection of antiviral siRNA sequences, delivery techniques to the infection sites, and provides an overview of antiviral siRNAs against respiratory viruses. Abstract : Pulmonary delivery of siRNA holds great promise for inhibiting respiratory virus replication particularly when antiviral drugs and vaccines are not yet available. This progress report discusses previous attempts of silencing respiratory viruses by highlighting the choice of target gene regions, the opportunities for the field of siRNA delivery and challenges in the development of inhalable siRNA formulations, particularly against SARS‐CoV‐2.